Identification of potent and selective retinoic acid receptor gamma (RARγ) antagonists for the treatment of osteoarthritis pain using structure based drug design. Issue 14 (15th July 2016) - Hughes, Norman E.; Bleisch, Thomas J.; Jones, Scott A.; Richardson, Timothy I.; Doti, Robert A.; Wang, Yong; Stout, Stephanie L.; Durst, Gregory L.; Chambers, Mark G.; Oskins, Jennifer L.; Lin, Chaohua; Adams, Lisa A.; et al.
Graphical abstract: Abstract: A series of triaryl pyrazoles were identified as potent pan antagonists for the retinoic acid receptors (RARs) α, β and γ. X-ray crystallography and structure-based drug design were used to improve selectivity for RARγ by targeting residue differences in the ligand binding pockets of these receptors. This resulted in the discovery of novel antagonists which maintained RARγ potency but were greater than 500-fold selective versus RARα and RARβ. The potent and selective RARγ antagonist LY2955303 demonstrated good pharmacokinetic properties and was efficacious in the MIA model of osteoarthritis-like joint pain. This compound demonstrated an improved margin to RARα-mediated adverse effects.